PEMERIKSAAN MIKROSKOP DAN TES DIAGNOSTIK CEPAT DALAM MENEGAKKAN DIAGNOSIS MALARIA - Wijaya Kusuma; A.A. Wiradewi Lestari; Sianny Herawati; I Wayan Putu Sutirta Yasa (E-Jurnal Medika Udayana, 2014)
Malaria is an infection disease caused by plasmodium parasite that transmitted to humanbody by female anopheles mosquito bites. World Health Organization (WHO) predictedthat 3,3 billion people around the world were at risk to infected by malaria in 2006 andalmost 1 million died because of this disease. Diagnosis of malaria according to clinicalmanifestation only is not specific; therefore it is less reliable and should be s upported bylaboratory examination result. Microscopic examination of blood smear and rapiddiagnostic test are most often used to diagnose malaria. Both of this test gave big chance tomake accurate diagnostic but still have their own limitations.